2008
DOI: 10.1002/ajim.20557
|View full text |Cite
|
Sign up to set email alerts
|

Decreased lung function among employees at Norwegian smelters

Abstract: Compared with non-exposed employees, impairment of lung function among employees at Norwegian smelters was significantly related to the job categories of line operator and non-line operator.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
2

Year Published

2008
2008
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(27 citation statements)
references
References 27 publications
1
24
2
Order By: Relevance
“…The associations between the prevalence of airflow limitation and covariates using repeated measurements and the corresponding results from the baseline data were very similar 3. In contrast to the cross-sectional analyses of baseline data, analyses using repeated measurements yielded significant results regarding the association between the prevalence of airflow limitation and the job categories, probably due to increased power.…”
Section: Discussionmentioning
confidence: 60%
See 1 more Smart Citation
“…The associations between the prevalence of airflow limitation and covariates using repeated measurements and the corresponding results from the baseline data were very similar 3. In contrast to the cross-sectional analyses of baseline data, analyses using repeated measurements yielded significant results regarding the association between the prevalence of airflow limitation and the job categories, probably due to increased power.…”
Section: Discussionmentioning
confidence: 60%
“…During production various air pollutants are emitted to the workplace environment, primarily particulates and gases potentially harmful to the airways 1 2. In a cross-sectional study of employees in this industry, we found that subjects who worked full-time on the production line (line operators) had lower lung function expressed as forced expiratory volume in 1 s (FEV 1 ) as well as forced vital capacity (FVC) compared with unexposed workers 3. Moreover, longitudinal analyses showed that they also had a steeper annual decline in FEV 1 compared with unexposed workers 4.…”
Section: Introductionmentioning
confidence: 99%
“…The PM may be harmful if inhaled and exposure to high levels of particles has been linked to cancer, pneumonia, chronic obstructive pulmonary disease (COPD) and other respiratory and cardiovascular syndromes. [79][80][81][82][83][84][85][86] Almost all processes involved in silicon alloy production produces PM in some form. In this article, the terms particulate matter and dust are used as synonyms and primarily used for solid particles.…”
Section: Particulate Emissionsmentioning
confidence: 99%
“…Details of the spirometry measurements can be found elsewhere (10). Airflow limitation was expressed as a FEV 1 /FVC ratio that was less than the lower limit of normal (ie, below the 5th percentile of the predicted value as the lower limit) (10). The questionnaire also included questions about smoking habits, previous exposure to dust and gases, and a description of job tasks during the last 12 months.…”
Section: Study Population and Methodsmentioning
confidence: 99%
“…The maximum acceptable variation between the best and the second best measurement of the forced vital capacity (FVC) was 5% or 100 ml, whichever was the highest. Details of the spirometry measurements can be found elsewhere (10). Airflow limitation was expressed as a FEV 1 /FVC ratio that was less than the lower limit of normal (ie, below the 5th percentile of the predicted value as the lower limit) (10).…”
Section: Study Population and Methodsmentioning
confidence: 99%